2018
DOI: 10.1155/2018/9828725
|View full text |Cite
|
Sign up to set email alerts
|

Cortical AAV-CNTF Gene Therapy Combined with Intraspinal Mesenchymal Precursor Cell Transplantation Promotes Functional and Morphological Outcomes after Spinal Cord Injury in Adult Rats

Abstract: Ciliary neurotrophic factor (CNTF) promotes survival and enhances long-distance regeneration of injured axons in parts of the adult CNS. Here we tested whether CNTF gene therapy targeting corticospinal neurons (CSN) in motor-related regions of the cerebral cortex promotes plasticity and regrowth of axons projecting into the female adult F344 rat spinal cord after moderate thoracic (T10) contusion injury (SCI). Cortical neurons were transduced with a bicistronic adeno-associated viral vector (AAV1) expressing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 68 publications
(107 reference statements)
0
6
0
Order By: Relevance
“…The AAV1 serotype is commonly used to transduce the CST via intracortical injections [31][32][33][34][35][36][37][38]. An earlier study that compared seven AAV serotypes (AAV1-AAV6, and AAV8) identified AAV1 and AAV5 as the best and secondbest serotypes to transduce the CST in rats [20].…”
Section: The Aav1 Serotype For Transduction Of the Corticospinal Tracmentioning
confidence: 99%
“…The AAV1 serotype is commonly used to transduce the CST via intracortical injections [31][32][33][34][35][36][37][38]. An earlier study that compared seven AAV serotypes (AAV1-AAV6, and AAV8) identified AAV1 and AAV5 as the best and secondbest serotypes to transduce the CST in rats [20].…”
Section: The Aav1 Serotype For Transduction Of the Corticospinal Tracmentioning
confidence: 99%
“…Under a sterile condition, the T9-T11 laminae were removed by laminectomy, and then the T10 segment was compressed using a modified aneurysm clip at 20 g for 60 s. Pain was alleviated by analgesics, while the infection was prevented with antibiotics. Successful model establishment in rats was confirmed by a < 1 score 1 h after surgery according to a Basso, Beattie, and Bresnahan (BBB) locomotor rating scale [ 18 , 19 ]. The remaining 8 rats were subjected to sham operation with only the skin and muscle cut open and sutured.…”
Section: Methodsmentioning
confidence: 99%
“…Other potential treatment strategies using implanted MSCs include promoting neural differentiation (EGF, Shh and miR-124) [ 159 , 176 , 247 , 248 ]; enhancing proliferation (bFGF, PTEN, IGF-1, and Nice4, Fig. 6 ) [ 203 , [249] , [250] , [251] ]; increasing migration ability (ChABC, Snail, miR-31 and SDF-1α) [ 250 , [252] , [253] , [254] ]; inhibiting apoptosis (GIT1 and miR-21) [ 255 , 256 ]; reducing antioxidative stress (miR-200a) [ 256 ]; proangiogensis (miR-17-5p) [ 257 ]; and neurotrophic effect (CNTF, BDNF, miR-146a-5p and miR-383) [ [258] , [259] , [260] , [261] , [262] ]. The details of these transgenic MSCs for SCI treatment are summarized in Table 2 .…”
Section: Gene Transfer Into Mscs For Neurological Disease Treatmentmentioning
confidence: 99%